2013
DOI: 10.1182/blood-2013-03-492454
|View full text |Cite
|
Sign up to set email alerts
|

IRP1 regulates erythropoiesis and systemic iron homeostasis by controlling HIF2α mRNA translation

Abstract: Key Points• IRP1 controls HIF2a mRNA translation in vivo and thereby acts as an upstream regulator of Epo expression. • IRP1 deficiency leads to age-dependent erythropoietic abnormalities and misregulation of body iron metabolism via the HIF2a/Epo pathway.Hypoxia inducible factor 2a (HIF2a) transcriptionally activates several genes in response to hypoxia. Under normoxic conditions, it undergoes oxygen-dependent degradation by the prolyl hydroxylase (PHD)/von Hippel-Lindau (VHL) system. The presence of an iron-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(116 citation statements)
references
References 48 publications
4
104
3
1
Order By: Relevance
“…Another iron-dependent antioxidant ACO1 displayed elevated mRNA levels under both protective regimens in our study. ACO1, also known as iron-regulatory protein 1 (IRP1), has been demonstrated to serve as a key upstream regulator of HIF2a (50). Accordingly, the Hif2a transcript was also increased in both protective regimens.…”
Section: Discussionmentioning
confidence: 81%
“…Another iron-dependent antioxidant ACO1 displayed elevated mRNA levels under both protective regimens in our study. ACO1, also known as iron-regulatory protein 1 (IRP1), has been demonstrated to serve as a key upstream regulator of HIF2a (50). Accordingly, the Hif2a transcript was also increased in both protective regimens.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, Irp1 −/− mice exhibit features of Hif2a overexpression and hyperproduction of Epo, while Irp1 constitutive transgenic mice show defects in erythroid differentiation that can be attributed to decreased Hif2a expression. [113][114][115] These observations indicate that Irp1 acts as an iron and oxygen sensor, linking iron metabolism with erythropoiesis via EPO. In iron deficiency, Irp1 suppresses HIF2a and Epo expression to reduced iron availability, consistently with iron-restricted erythropoiesis.…”
mentioning
confidence: 92%
“…123 In addition, Fpn, divalent metal transporter 1 (Dmt1) and apical ferric reductase duodenal cytochrome B (DcytB) in the dudodenum are regulated by hypoxia and intracellular iron concentration. 112,115,161,162 It has been shown that expression of the Dmt1, DcytB and Fpn are increased in the duodenum of Hbb th3/+ mice as a consequence of hypoxia and Hif2a stabilization and activity. 112,162 In fact, Hbb th3/+ mice showed improvement in tissue-iron levels and anemia following genetic ablation of intestinal Hif2a.…”
Section: Hif2a Inhibitorsmentioning
confidence: 99%
“…However, mice in which IRP-1 alone was knocked out did not have an immediate apparent phenotype, suggesting that IRP-1 and IRP-2 have redundant physiologic functions (i.e., IRP-2 rescues the deficiency of IRP-1) (50). However, detailed inspection found that mice with targeted deletion of IRP-1 developed polycythemia (51,52) and spontaneous PH (53). This response was found to be due to translational derepression of HIF2a, with a subsequent increase in erythropoietin and endothelin-1 (a potent pulmonary vascular bed constrictor involved in the development of PH [54]).…”
Section: Iron Regulatory Proteins and Iron Responsive Elementsmentioning
confidence: 99%